Greenium as a factor in strategic Green Bond issuance : Empirical evidence from the European markets - Karinen, Julia (My University, 2025)
The climate crisis is one of the most pressing challenges of our time, demanding immediate and scalable solutions. While international agreements such as the Paris Agreement have laid the foundation for global climate action, the role of financial markets—and particularly market-based instruments—has grown increasingly vital. Among these, green bonds have emerged as a key tool to mobilize capital toward sustainable and environmentally aligned projects. As these instruments continue to evolve, questions remain regarding their pricing behavior and the so-called “greenium”, a premium that reflects investor preference for green over conventional bonds. This thesis investigates the existence and key drivers of the greenium in the European primary green bond market. While previous research has largely focused on verifying whether a greenium exists, this study expands the discussion by examining the internal (bond-specific) and external (market-driven) factors that may influence its magnitude. Using a matched dataset of 64 green and conventional bonds issued between 2014 and 2024, the thesis applies a quantitative analysis to uncover patterns in how green bonds are priced relative to their conventional counterparts. The findings confirm an average greenium of 6 basis points, aligning with results from earlier studies. Three statistically significant drivers were identified: the risk-free rate, the issuer’s credit rating, and the bond’s coupon size. Specifically, higher market rates and stronger credit ratings are associated with smaller greeniums, while larger coupon sizes increase the premium. Other factors, including market volatility and issuance volume, did not show statistically significant influence in this dataset. These results suggest that the greenium is not a fixed or uniform phenomenon, but rather a dynamic outcome influenced by shifting market conditions and issuer characteristics. The thesis contributes to the existing literature by offering an updated and focused analysis of greenium in Europe’s maturing green bond market, with practical implications for both issuers and investors navigating sustainable finance strategies. In doing so, it strengthens the understanding of green bonds as a potentially cost-effective and climate-conscious financing mechanism—and one that may play a critical role in the broader transition toward a low-carbon economy.

Ilmastokriisi on yksi aikamme keskeisimmistä haasteista ja vaatii välittömiä sekä laajamittaisia ratkaisuja. Vaikka kansainväliset sopimukset, kuten Pariisin ilmastosopimus, ovat luoneet perustan globaalille ilmastotoiminnalle, rahoitusmarkkinoiden ja erityisesti markkinapohjaisten ratkaisuiden rooli on kasvanut yhä merkittävämmäksi. Näistä vihreät joukkovelkakirjat ovat nousseet keskeiseksi työkaluksi, jolla pääomaa ohjataan ympäristön kannalta kestäviin hankkeisiin. Koska kyseessä on suhteellisen uusi rahoitusinstrumentti, vihreiden joukkovelkakirjojen hinnoitteluun ja niin sanottuun "vihreään preemioon" (greeniumiin) liittyy edelleen avoimia kysymyksiä. Tämä tutkielma tarkastelee vihreän preemion olemassaoloa ja sen taustalla vaikuttavia tekijöitä Euroopan vihreiden joukkovelkakirjojen primäärimarkkinoilla. Aiempi tutkimus on keskittynyt lähinnä greeniumin olemassaolon todentamiseen, mutta tämä työ laajentaa näkökulmaa analysoimalla sen sisäisiä (velkakirjakohtaisia) ja ulkoisia (markkinaperusteisia) ajureita. Kvantitatiivinen analyysi perustuu 64 vihreän ja vastaavan perinteisen joukkovelkakirjan muodostamaan aineistoon vuosilta 2014–2024. Tulokset osoittavat, että keskimääräinen greenium on noin 6 korkopistettä, mikä on linjassa aiemman tutkimuskirjallisuuden kanssa. Tilastollisesti merkitseviksi tekijöiksi nousivat riskitön korko, liikkeeseenlaskijan luottoluokitus sekä joukkovelkakirjan kuponkikorko. Korkeampi markkinakorkotaso ja vahvempi luottoluokitus liittyivät pienempään greeniumiin, kun taas suurempi kuponkikorko lisäsi preemion suuruutta. Muut tarkastellut tekijät, kuten markkinavolatiliteetti ja liikkeeseenlaskujen kokonaismäärä markkinalla, eivät osoittautuneet merkittäviksi tässä aineistossa. Havainnot osoittavat, että greenium ei ole yhtenäinen tai kiinteä ilmiö, vaan se vaihtelee markkinaolosuhteiden ja liikkeeseenlaskijoiden ominaisuuksien mukaan. Tutkielma tarjoaa ajankohtaisen ja syventävän katsauksen vihreiden joukkovelkakirjojen hinnoitteluun Euroopassa ja tarjoaa samalla käytännön näkökulmia sekä liikkeeseenlaskijoille että sijoittajille. Samalla se vahvistaa ymmärrystä vihreistä joukkovelkakirjoista kustannustehokkaana ja ilmastoystävällisenä rahoituskeinona, jolla voi olla tärkeä rooli siirryttäessä kohti vähähiilistä taloutta.
Keywords: green bond, greenium, sustainable finance, sustainable development, vihreä joukkovelkakirjalainen, greenium, vihreä rahoitus, kestävä kehitys